1999
DOI: 10.1002/(sici)1097-0142(19990815)86:4<608::aid-cncr9>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid carcinoma of the lung

Abstract: BACKGROUND Spindle and giant cell carcinomas of the lung are rare subtypes and are regarded as one type of lung carcinoma, termed pleomorphic carcinoma in the Armed Forces Institute of Pathology classification. This classification is different from the World Health Organization classification. METHODS Thirty‐seven cases of sarcomatoid (spindle and/or giant cell) carcinoma of the lung were studied by light microscopy, conventional histochemistry, and immunohistochemistry to establish their clinical and histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(31 citation statements)
references
References 39 publications
1
26
0
1
Order By: Relevance
“…Interestingly, we also identified 2 patients with combination mutations. One patient had EGFR and TP53 mutations, and the other had an EML4-ALK gene fusion and a TP53 mutation, which have rarely been described in PSC tumors 21 . Several studies have suggested that the reversion of functional TP53 can trigger tumor cell death and lead to tumor clearance, even if a tumor carries multiple genetic alterations that drive tumor growth 27, 28 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Interestingly, we also identified 2 patients with combination mutations. One patient had EGFR and TP53 mutations, and the other had an EML4-ALK gene fusion and a TP53 mutation, which have rarely been described in PSC tumors 21 . Several studies have suggested that the reversion of functional TP53 can trigger tumor cell death and lead to tumor clearance, even if a tumor carries multiple genetic alterations that drive tumor growth 27, 28 .…”
Section: Discussionmentioning
confidence: 90%
“…Histology and immunohistochemistry are the gold standards for the diagnosis of PSC. Regarding immunohistochemistry, CEA, EMA, CK, CK7, chromogranin A, CD56, and synaptophysin can be used as markers for carcinomatous components, and desmin, vimentin, and smooth muscle/sarcomeric actin can be used as markers for sarcomatous elements 17, 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis remains controversial. Although some insist that the prognosis of PSC is less favorable than other NSCLC among postoperative patients [1,5,6], others see no difference between PSC and other NSCLC [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…The average age at diagnosis is 60 to 65 years [1, 3, 515]. Several studies suggested an increased male prevalence [1, 2, 4, 5, 8, 11], while others, including the largest epidemiologic study to date using the Surveillance, Epidemiology, and End Results database, suggested a nearly 1-to-1 gender ratio [3, 12]. Sarcomatoid carcinoma is associated with heavy tobacco smoking history [1, 9, 15].…”
Section: Discussionmentioning
confidence: 99%